A two-component model for the high-energy variability of blazars: application to PKS 2155-304 - Reynoso, Matias Miguel (2012)
Aims. We study the production of VHE emission in blazars as a superposition of a steady component from a baryonic jet and a time-dependent contribution from an inner e− e+ beam launched by the black hole. Methods. Both primary relativistic electrons and protons are injected in the jet, and the particle distributions along it are found by solving a one-dimensional transport equation that accounts for convection and cooling. The short-timescale variability of the emission is explained by local pair injections in turbulent regions of the inner beam. Results. For illustration, we apply the model to the case of PKS 2155-304, reproducing a quiescent state of emission with inverse Compton and synchrotron radiation from primary electrons, as well as proton-proton interactions in the jet. The latter also yield an accompanying neutrino flux that could be observed with a new generation km-scale detector in the northern hemisphere such as KM3NeT.